(untitled) (GEON Journal (Management, Organizations and Business), 2016)
The psicografia involves the use of psychological and anthropological factors to determine how the market is segmented considering trends within that market groups to make a decision about a product, a person, an ideology or anything else that makes a attitude or use half. Psychographic profiles describe the characteristics and responses of an individual to an environment. From market segmentation to define the target market psicografia, create a new perspective of the market, the product positioning, better communicate product attributes, develop overall strategies , market and social policy issues. Psicograficamente segmenting consumers are divided according to: lifestyle, personality and values. The Colombian Caribbean is composed of eight departments (La Guajira, Atlantico, Bolivar, Cesar, Córdoba, Magdalena, Sucre and San Andrés and Providencia, Santa Catalina), in addition to its climatic and geographical differences , there is a relevant factor in the pattern of consumption and cultural features of its inhabitants. This is determined by their pre-Columbian ancestor; as were the Spanish conquest and the presence of African slaves and cultural, regional features they are merged and therefore the consumption characteristics of these inhabitants.